Compensatory growth response of Catla catla (Hamilton, 1822) juveniles, stunted with varied stocking density and photoperiod, in subsequent grow-out phase - Sahoo, P. R.; Das, P. C.; Nanda, S.; Sahu, B.; Muduli, L. (Indian Journal of Fisheries, 2021)
Stunted juveniles of Catla catla (Hamilton, 1822) were produced through 150 days of stunting with five combinations of density and photoperiod. These stunted juveniles were subsequently polyculturedÂ in grow-out ponds for eight months along with rohu (Labeo rohita) and mrigal (Cirrhinus mrigala). In grow-out trial, the five treatments with different combinations of stocking density and photoperiod comprised, Â control (20 m-3, 12L/12D), T-1 (30 m-3, 12L/12D), T-2 (40 m-3, 12L/12D), T-3 (20 m-3, 6L/18D) and T-4 (20 m-3, 0L/24D). After eight months of culture, growth curves of stunted catla in all treatments were non-convergent and inferior to control, indicating no compensatory growth response. Although survival (70-73%), average body weight, (ABW; 667-755 g) and weight gain (648-729 g) in grow-out phase were statistically similar in the groups with different stocking density (Control, T-1 and T-2) (p>0.05), the grow-out survival was relatively higher in T-2 (73.3%), indicating its positive correlation with higher stunting density. In contrast, juveniles stunted with reduced photoperiod (T-3 and T-4) showed significantly lower ABW and weight gain (p<0.05). The poor survival in T-3 and T-4 (40-43%) indicated significant effect of stunting with reduced photoperiod on subsequent grow-out survival and yield performance. Based on the results, the study recommend the use of rearing density up to 40 m-3 for juvenile stunting in catla. Keywords: Catla, Compensatory growth, Fish culture, Mixed fish farming, Stunted fish Â